Design Professional Rice Business in Tabanan Regency - I Gusti Bagus Udayana; Gede Sedana; I Ketut Sunadra (SEAS (Sustainable Environment Agricultural Science), 2018)
Rice is the main food ingredient of the people of Indonesia. Rice is used primarily to be processed into rice, and a variety of other foods. Every day, households need rice for consumption. This is what makes the velocity of money in the business of rice is very fast. Rice itself has various types and levels of quality. Every kind of rice certainly has a different price. Thus, each consumer determines the kind of rice to be consumed. In Tabanan regency, agriculture is a very potential field, so it is included in the category of excellent potentials, especially food crops such as rice. Since 2013, the Government of Tabanan Regency has planned agricultural programs that implement organic farming systems on paddy fields. Everyone needs rice because this product is the staple food of the people, especially Indonesian citizens from the start of small children, adolescents, until the parents need rice as the main ingredient of him every day. Therefore the tremendous business opportunity of selling rice will never end. The resulting product is called "Healthy Rice Tabanan." The program aims to ensure market certainty and favorable pricing for established farmers and adopt a farming system free of synthetic chemicals to produce environmentally friendly and healthy rice for consumers. The grain market chain produced by farmers is very short so that the grant share earned by farmers is also high. The market chain is from Farmers to Perpadi and Consumers (including Tabanan District Officers). The results showed that healthy rice business conducted between farmers and consumers and consumers had not shown a fair, professional rice business because there are no agreements and contracts that guide various parties to carry out their business. Therefore, the expected fair trade cannot be appropriately realized at the implementation level. Thus, in the context of the fair trade system of rice in Tabanan Regency, it is necessary to have the concept of inclusive business (professional business) to encourage fair trade.